2001
DOI: 10.1536/jhj.42.339
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Endothelial Nitric Oxide Production by Chenodeoxycholic Acids in Patients with Hepatobiliary Diseases.

Abstract: SUMMARYThe purpose of this study was to clarify whether physiological concentrations of bile acids could affect endothelial nitric oxide production. We investigated the relationships between clinical concentrations of individual bile acids observed in patients with hepatobiliary diseases and endothelial nitric oxide production induced by each bile acid.Fifteen serum bile acids were measured using high-performance liquid chromatography combined with enzymatic fluorometry in 8 patients with liver cirrhosis, obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…These results are consistent with studies evaluating NO‐mediated bile acid damage and chronic inflammation within the gastrointestinal tract, including one recent report that iNOS knock‐out mice were resistant to deoxycholate‐induced colitis 54. Although esophageal tissues and cell lines had not been evaluated specifically, previous studies have reported increased NO production following exposure to bile acids 55, 56, possibly through increased intracellular Ca 2+ concentrations 57, 58.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with studies evaluating NO‐mediated bile acid damage and chronic inflammation within the gastrointestinal tract, including one recent report that iNOS knock‐out mice were resistant to deoxycholate‐induced colitis 54. Although esophageal tissues and cell lines had not been evaluated specifically, previous studies have reported increased NO production following exposure to bile acids 55, 56, possibly through increased intracellular Ca 2+ concentrations 57, 58.…”
Section: Discussionsupporting
confidence: 88%
“…(21) The most hydrophobic bile acid LCA was not detected in the sera of either healthy subjects or liver cirrhosis patients. (8) The serum concentrations of total bile acid, CDCA, UDCA and CA were markedly higher in patients with hepatobiliary diseases than in healthy subjects. Among these bile acids, CDCA, both free acid and its conjugates, was particularly increased.…”
Section: Discussionmentioning
confidence: 92%
“…Among these bile acids, CDCA, both free acid and its conjugates, was particularly increased. (8) Serum DCA concentrations were shown to be markedly lower than those of the above bile acids in both healthy subjects and patients. (8) GCDCA and TUDCA had relatively lower hydrophobicity with R MW values of 2.92 and 1.71, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations